2021
DOI: 10.3390/ijerph182111578
|View full text |Cite
|
Sign up to set email alerts
|

Work along Both Lines: The Positive Impact of Work-Based Social Media Use on Job Performance

Abstract: Social media has rapidly become an important tool in organizations and has a significant impact on employees’ work and organizational operations. By applying social media to their daily work, employees gain access to important information resources that can help them get things done. Using the conservation of resources theory, this study examines the impact of work resources generated by employees’ work-based social media use on work status, as well as job performance. Data were collected from the employees of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…As soon as we open our eyes, we immediately receive updates on our smartphones (Chandel, 2018) However, it is also becoming more common in the workplace for office stuff, including communication, coordination, and others (Lee & Lee, 2020). Social media, however, has both positive (Zhao, Guo, Shang & Wang, 2021) and negative impacts, including problems caused by excessive and ineffective use, as well as a decline in well-being and productivity at work (Shakki, Nia & Bai, 2019). In this regard, Danial Goleman has popularized EI skill in relation to common emotions.…”
Section: The Discussion and Resultsmentioning
confidence: 99%
“…As soon as we open our eyes, we immediately receive updates on our smartphones (Chandel, 2018) However, it is also becoming more common in the workplace for office stuff, including communication, coordination, and others (Lee & Lee, 2020). Social media, however, has both positive (Zhao, Guo, Shang & Wang, 2021) and negative impacts, including problems caused by excessive and ineffective use, as well as a decline in well-being and productivity at work (Shakki, Nia & Bai, 2019). In this regard, Danial Goleman has popularized EI skill in relation to common emotions.…”
Section: The Discussion and Resultsmentioning
confidence: 99%
“…Chen et al [ 107 ] found that using internal or external social media for work purposes could improve employee performance; using external social media for social purposes could also improve employee performance because of reduced fatigue, but using internal social media could lead to a decrease in performance because of distraction from work tasks. Zhao et al [ 108 ] concluded that this behavior can positively affect employee performance by increasing work engagement and reducing work interruptions. Wu et al [ 109 ] found that employees’ use of social media triggered job stress and that challenging stress contributed to employee performance, while hindering stress had a negative effect.…”
Section: Discussionmentioning
confidence: 99%
“…The third variable is work engagement. Zhao et al [ 108 ] found that this behavior increased work engagement and reduced work interruptions, thus achieving increased employee performance. Cheng et al [ 94 ] found that this behavior stimulated work engagement, which in turn stimulated employees’ innovative performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, corporations that engage in business-to-consumer activities extensively leverage social media platforms as a component of their digital transformation and reap the advantages thereof, including but not limited to increased revenues, heightened brand recognition and enhanced consumer interaction (Harrigan et al ., 2020; Barreda et al ., 2015). The association between social media and better work performance has been attributed to the better connections and access to various resources that social media provides to workers, thereby facilitating their job performance (Zhao et al ., 2021; Song et al ., 2019; Moqbel and Kock, 2018). Additionally, empirical evidence has established that social media platforms bolster self-esteem and contentment among young adult populations (Acun, 2020; Hawi and Samaha, 2017; Steinfield et al ., 2008).…”
Section: Literature Reviewmentioning
confidence: 99%